Strategi Penguatan Rantai Nilai Komoditas Sayuran Unggulan pada Kelompok Tani Sukorambi Jaya Kabupaten Jember - Moh Ilham Fahmi Fadjar (Fakultas Teknologi Pertanian, 2026)
Vegetable commodities play an important role in fulfilling food needs and serving as a source of income for farmers. However, vegetable marketing in the Sukorambi Jaya Farmer Group still faces several constraints, such as dependence on collectors, limited access to direct markets, suboptimal postharvest handling, the absence of product identity, and weak bargaining power in price determination. These conditions cause the selling prices and profits received by farmers to remain less than optimal. This study aimed to determine the leading vegetable commodity, map the value chain of the selected commodity, and formulate an appropriate marketing strategy to strengthen the vegetable value chain in the Sukorambi Jaya Farmer Group. The methods used in this study included the Fuzzy Analytical Hierarchy Process (Fuzzy AHP) to determine the leading commodity, Value Chain Mapping using Porter's model to analyze value chain activities, and SWOT analysis through the IFE and EFE matrices to formulate marketing strategies. The results showed that mustard greens were selected as the leading vegetable commodity with the highest weight of 0.471. The value chain of mustard greens involved farmers, collectors, wholesalers or retailers, and consumers. Farmers were still dominant in production activities, while activities supporting product quality and marketing performance, such as sorting, packaging, product labeling, price recording, and direct selling, remained limited. The SWOT analysis placed the Sukorambi Jaya Farmer Group in Quadrant or the Strength-Opportunities (S-O) position. The recommended strategies include establishing a farmer group marketing unit, developing simple packaging, collaborating with agricultural extension officers, implementing collective selling, strengthening reference prices, and expanding distribution channels. These strategies are expected to be implemented gradually to strengthen farmers' bargaining position, improve marketing effectiveness, and enhance the value chain performance of mustard greens.
:: Finalisasi repositori 14 Juli 2026_Kurnadi
Keywords: Fuzzy AHP; rantai nilai; sawi hijau; strategi pemasaran; SWOT